Conspecific and not performance‐based attraction on immigrants drives colony growth in a waterbird. (19th June 2017) - Tenan, Simone; Fasola, Mauro; Volponi, Stefano; Tavecchia, Giacomo
Abstract: Local recruitment and immigration play an important part in the dynamics and growth of animal populations. However, their estimation and incorporation into open population models is, in most cases, problematic. We studied factors affecting the growth of a recently established colony of Eurasian spoonbill ( Platalea leucorodia ) and assessed the contribution of local recruits, i.e. birds born in the colony, and immigrants, i.e. birds of unknown origin, to colony growth. We applied an integrated population model that accounts for uncertainty in breeding state assignment and merges population surveys, local fecundity and individual longitudinal data of breeding and non‐breeding birds, to estimate demographic rates and the relative role of recruitment and immigration in driving the local dynamics. We also used this analytical framework to assess the degree of support for the 'performance‐based' and 'conspecific attraction' hypotheses as possible mechanisms of colony growth. Among the demographic rates, only immigration was positively and significantly correlated with population growth rate. In addition, the number of immigrants settling in the colony was positively correlated with colony size in the previous and current year, but was not correlated with fecundity of the previous year. Our results suggest that the variation in immigration affected colony dynamics and that conspecific attraction likely triggered the relevant role of immigration in the growth of a recently formed waterbird colony, supporting the need of including immigration in population analysis. Abstract : The authors show that immigration, but not local recruitment, can drive the growth of a recently established waterbird colony. They also bring evidence for conspecific attraction as a factor affecting settlement decision of immigrants. The results support the need of including immigration in population analysis, using suitable analytical approaches.